Factors Associated with Intention to Donate Hematopoietic Stem Cells among Blood Donors - Chuo, Yew Ting; Yew, Fong Lee; Chien, Joo Lim; Sing, Rachel Kiat Ting; Mohammad Masrin, MD Zahrin; Abu Sufian, Ahmad; Siew, Jack Yu Wong; Masita, Arip; Zubaidah, Zakaria; Shahren, Ahmad Zaidi Adruce; Koh, Jessie Sing Tnay; Yi, Shen Wong (Karger AG, Basel, 2020)
Introduction: Past studies pay little attention to the inten-tion to donate hematopoietic stem cells (HSC) among blood donors. This study investigated the level of and the influence of socio-demographic characteristics, knowledge, attitude, subjective norm and self-efficacy on the intention to donate HSC among blood donors. Methods: This cross-sectional study recruited blood donors at selected public hospitals in the Malaysian State of Sarawak in 2019. A structured ques-tionnaire was developed based on the review of relevant lit-erature. It gathered information on socio-demographic characteristics, knowledge, attitude, subjective norm and self-efficacy on the intention to donate HSC. Variables with a p value <0.200 in bivariate analysis were included in the variable selection for regression modeling to examine their associations with the intention to donate HSC. Results: A to tal of 569 blood donors participated (94.5% response rate). Overall, 87.1% reported a positive intention to donate HSC. In the regression model, the factor with the greatest associa-tion with intention to donate HSC was subjective norms about HSC donation (β = 0.35, 95% CI 0.27–0.42), followed by attitude about regulations of HSC donation (β= 0.21, 95% CI 0.13–0.35), self-efficacy on HSC donation (β = 0.15, 95% CI 0.09–0.32), attitude about the potential side effects of HSC donation (β = 0.14, 95% CI 0.02–0.10) and highest education level (β = 0.10, 95% CI 0.03–0.44). Conclusions: The findings can be used to formulate a better strategy in promoting HSC donation among blood donors in the region